2007
DOI: 10.1002/bjs.5779
|View full text |Cite
|
Sign up to set email alerts
|

Life-saving therapy for haemorrhaging liver adenomas using selective arterial embolization

Abstract: Selective embolization of the hepatic artery is a safe and adequate first approach in the management of patients with haemorrhaging hepatocellular adenomas. Furthermore, arterial embolization reduces the size of adenomas in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…[15][16][17][18] Unlike HCA, FNH carries no risk of bleeding and malignant transformation and therefore, 19 the need for resection is rare, and is only dictated by symptoms. The same holds for haemangioma.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Unlike HCA, FNH carries no risk of bleeding and malignant transformation and therefore, 19 the need for resection is rare, and is only dictated by symptoms. The same holds for haemangioma.…”
Section: Introductionmentioning
confidence: 99%
“…If malignancy cannot be excluded, surgical resection is preferred. Selective arterial embolization can be used both as an elective treatment to reduce the size of the HCA as well as the initial emergency treatment in case of active bleeding of the HCA [24][25][26]. It is a minimal invasive and safe procedure compared to laparotomy and complications are rare.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, mainly performed in different Dutch centers, TAE has been shown to lead to hemodynamic stabilization in selected patients with acceptable morbidity and possible beneficial effect on tumor size [15,17,18,19,20,21,25]. An emergency surgical resection with accompanying high morbidity and mortality, and possibly also secondary resection, can be avoided.…”
Section: Management Of Ruptured Hamentioning
confidence: 99%
“…However, it is important to realize that only a selected patient group in a center with adequate radiological experience can be treated with TAE. In a series from our own center, 10 of 11 patients with ruptured HA were stabilized after a single TAE, while 1 other patient needed three TAEs [20]. No emergency resections were needed and only minor complications were found (an example is shown in figure 2).…”
Section: Management Of Ruptured Hamentioning
confidence: 99%
See 1 more Smart Citation